2003
DOI: 10.1238/physica.regular.067a00500
|View full text |Cite
|
Sign up to set email alerts
|

Excitation Cross Sections for Li-like Ions of Beryllium and Boron

Abstract: We report on calculation of electron-impact excitation cross sections for Li-like ions of boron and beryllium. The data were produced with a number of modern methods in atomic collision theory, such as convergent close-coupling, K-matrix and Coulomb-Born-exchange. The results obtained are compared with other calculations and available expermental data, and the recommended cross sections for all transitions between atomic terms with principal quantum numbers n 4 are presented as tables of fitting parameters.Due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…For higher-Z ions (Z ≥ 4), a detailed comparison of all excitation cross sections between the states with the principal quantum number n ≤ 4 has shown that the CCC data practically coincide with the perturbative Coulomb-Born-exchange calculations [18]. Furthermore, a recent paper on electron-impact excitation in Be II and B III (also including the transitions between the excited states up to n ≤ 4) again demonstrated a high level of agreement between the CCC and the K-matrix cross sections [17]. Thus, the available data comparisons indicate that the CCC method seems to provide high accuracy for the excitation cross sections of Li-like ions and, correspondingly, for the inelastic contributions to the collisional line broadening.…”
Section: Theorymentioning
confidence: 64%
See 1 more Smart Citation
“…For higher-Z ions (Z ≥ 4), a detailed comparison of all excitation cross sections between the states with the principal quantum number n ≤ 4 has shown that the CCC data practically coincide with the perturbative Coulomb-Born-exchange calculations [18]. Furthermore, a recent paper on electron-impact excitation in Be II and B III (also including the transitions between the excited states up to n ≤ 4) again demonstrated a high level of agreement between the CCC and the K-matrix cross sections [17]. Thus, the available data comparisons indicate that the CCC method seems to provide high accuracy for the excitation cross sections of Li-like ions and, correspondingly, for the inelastic contributions to the collisional line broadening.…”
Section: Theorymentioning
confidence: 64%
“…Indeed, it was confirmed in a number of publications that the CCC excitation cross sections agree well with both the experimental data and other theoretical non-perturbative results for the ground state excitations. Such comparisons were done, e.g., for the R-matrix with pseudostates and K-matrix method results [15,16,17]. For higher-Z ions (Z ≥ 4), a detailed comparison of all excitation cross sections between the states with the principal quantum number n ≤ 4 has shown that the CCC data practically coincide with the perturbative Coulomb-Born-exchange calculations [18].…”
Section: Theorymentioning
confidence: 99%
“…The energies of the levels and (if available) the oscillator strengths were taken from the NIST database. A new improved set of CCC excitation and ionization cross sections for neutral beryllium as well as CCC data [14] for Be + were used. For selected transitions in Be, Be + and for ions Be 2+ , Be 3+ the cross sections were computed by the ATOM code [6] (the K-matrix for excitation and the normalized Coulomb-Born-exchange for ionization).…”
Section: Collisional-radiative Modelmentioning
confidence: 99%